Influence of pruning time on enhancing the yield and quality of Jasminum sambac flowers during off-season - NAIR, SUJATHA A; SUJATHA, K; VENUGOPALAN, R (The Indian Journal of Agricultural Sciences, 2011)
A study was made during 2005–08 to establish the effect of pruning time on flower induction in winter by pruning the plants at monthly intervals from August to November. The pooled data indicated highest flower yield in September pruned plants (72.99 g/plant) with good quality flower buds as compared to November pruned plants which produced only 25.51g/plant of marketable flower buds. The peak season yield was not affected by advancing the pruning time. Hence, September pruning enhances the yield and profitability due to higher prices realized in winter season.